2004
DOI: 10.1021/om049237k
|View full text |Cite
|
Sign up to set email alerts
|

Fluxional Behavior of a Perpendicularly Coordinated μ3-Alkyne Ligand on a Triruthenium Cluster. Synthesis and Structure of a μ322(⊥)-Cycloalkyne Complex

Abstract: Treatment of the triruthenium pentahydrido complex {Cp*Ru(μ-H)}3(μ3-H)2 (1; Cp* = η5-C 5Me5) with cycloalkene resulted in exclusive formation of the μ3-cycloalkyne complex {Cp*Ru(μ-H)}3(μ3-η2:η2(⊥)-C n H2 n - 4) (2a; n = 5, 2b; n = 6) as a result of vinylic C−H bond cleavage. VT NMR studies revealed fluxional behavior of the perpendicularly coordinated cycloalkyne ligand. Reaction of 2b with carbon monoxide afforded the 48-electron complex (Cp*Ru)3(μ-CO)(μ3-CO)(μ-H)(μ3-η2(∥)-C6H8) (3b) with a parallel-coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
4
24
0
1
Order By: Relevance
“…At 23°C, the time-averaged spectrum showing two sharp Cp * signals with the intensity ratio of 2:1 was obtained. Although the motion was not completely frozen even at À90°C, free energy of activation, DG à , at the coalescence temperature (6); Ru(1)-C(1), 2.124(4); Ru(1)-C(7), 2.065(4); Ru(1)-C(8), 1.998(4); Ru(2)-C(7), 2.066(3); Ru(2)-C(8), 2.030(4); Ru(2)-C(9), 1.965(4); Ru(3)-C(1), 2.387(4); Ru(3)-C(7), 2.176(4); Ru(3)-C(9), 2088(4); Ru(3)-H(1), 1.89(6); C(1)-C(2), 1.542 (5); C(1)-H(1), 1.00 (6); C(1)-H(2), 1.12 (5); C(2)-C(3), 1.547 (5); C(7)-O(1), 1.208(4); C(8)-O(2), 1.182(5); C(9)-O(3), 1.184(4); Ru(1)-Ru(2)-Ru (3), 59.629 (15); (2), 59.742 (12); Ru(2)-Ru(1)-Ru (3), 60.629 (14); Ru(1)-C(1)-C(2), 118.9(2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At 23°C, the time-averaged spectrum showing two sharp Cp * signals with the intensity ratio of 2:1 was obtained. Although the motion was not completely frozen even at À90°C, free energy of activation, DG à , at the coalescence temperature (6); Ru(1)-C(1), 2.124(4); Ru(1)-C(7), 2.065(4); Ru(1)-C(8), 1.998(4); Ru(2)-C(7), 2.066(3); Ru(2)-C(8), 2.030(4); Ru(2)-C(9), 1.965(4); Ru(3)-C(1), 2.387(4); Ru(3)-C(7), 2.176(4); Ru(3)-C(9), 2088(4); Ru(3)-H(1), 1.89(6); C(1)-C(2), 1.542 (5); C(1)-H(1), 1.00 (6); C(1)-H(2), 1.12 (5); C(2)-C(3), 1.547 (5); C(7)-O(1), 1.208(4); C(8)-O(2), 1.182(5); C(9)-O(3), 1.184(4); Ru(1)-Ru(2)-Ru (3), 59.629 (15); (2), 59.742 (12); Ru(2)-Ru(1)-Ru (3), 60.629 (14); Ru(1)-C(1)-C(2), 118.9(2).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in our previous communication, reaction of the (^)-cyclohexyne complex, {Cp * Ru(l-H)} 3 (l 3 -g 2 :g 2 (^)-cyclo-C 6 H 8 ) (3) with CO resulted in the formation of a (//)-cyclohexyne complex, (Cp * Ru) 3 (l 3 -g 2 -cyclo-C 6 H 8 )(l-H)(l-CO)(l 3 -CO) (4), with elimination of dihydrogen [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17] More recently, a reversed scheme termed switchback motion has been suggested to explain the fluxional behavior of the triruthenium cluster [{Cp*Ru(µ-H)} 3 (µ 3 ,η 2 :η 2 -C 5 H 6 )]. [18] We have monitored the isomerization of 3c to 4c by 1 H NMR spectroscopy and found that it is a very slow process at ambient temperature. After five months at ambient temperature, the mixture was heated in refluxing hexane for 4 h in order to obtain the equilibrium concentrations.…”
Section: Isomerism Of 3a-c To 4a-cmentioning
confidence: 99%